2019
DOI: 10.2196/12920
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Adoption in Mental Health: User Experience of a Mobile Health App for Patients With an Eating Disorder

Abstract: Background Despite the worldwide growth in mobile health (mHealth) tools and the possible benefits for both patients and health care providers, the overall adoption levels of mHealth tools by health professionals remain relatively low. Objective This study aimed (1) to investigate attitudes of health care providers and mHealth experts toward mHealth tools in the health context in general, and this study aimed (2) to test the acceptability and feasibility of a specific m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 47 publications
5
82
0
2
Order By: Relevance
“…If the application can collect data automatically and promptly without users’ frequent input, and be compatible with other devices and platforms (e.g., blood glucose-related applications and blood glucose monitors (or blood glucose pumps) [ 52 ], mobile phones and tablet computers, and Apple and Android systems [ 6 ]), it will enhance the use efficiency and affect the degree of user utilization and the willingness to use it continuously [ 50 ]. However, healthcare practitioners believe that heavy offline workloads restrict their time and effort to learn, adapt to, and use the application, even if they approve of it [ 53 ]. Furthermore, using the application in addition to familiar workflows may be disruptive, and they are concerned about extra workloads.…”
Section: Resultsmentioning
confidence: 99%
“…If the application can collect data automatically and promptly without users’ frequent input, and be compatible with other devices and platforms (e.g., blood glucose-related applications and blood glucose monitors (or blood glucose pumps) [ 52 ], mobile phones and tablet computers, and Apple and Android systems [ 6 ]), it will enhance the use efficiency and affect the degree of user utilization and the willingness to use it continuously [ 50 ]. However, healthcare practitioners believe that heavy offline workloads restrict their time and effort to learn, adapt to, and use the application, even if they approve of it [ 53 ]. Furthermore, using the application in addition to familiar workflows may be disruptive, and they are concerned about extra workloads.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, personalization was one of the features that lesser proportion of nurses needed to have in the mobile health application. Anastasiadou [51] showed that patients have different needs and characteristics and that mobile health applications need to be personalized.…”
Section: Resultsmentioning
confidence: 99%
“…One qualitative study compared the impact of TCApp between individuals with AN, BN, and EDNOS ( n = 9), mobile health experts ( n = 11), health care professionals ( n = 10), and ED specialists ( n = 8) [ 87 ]. TCApp is a mobile health app that connects children and adolescents with EDs with their therapists in the periods between medical consultation.…”
Section: Resultsmentioning
confidence: 99%